Estimating the Optimal Level of Public Debt for Economic Growth: An Evidence from Pakistan - Ashfaq, Muhammad; Padda, Ihtsham UlHaq (Quest Journal of Management and Social Sciences, 2019)
Background: In underdeveloped economies, the role of public debt is very vital with the intention of achieving a desirable level of output, employment and sustainability in long run economic growth. Fiscal deficit in developing economies is a common phenomenon because of low tax base and high imports. Economy of Pakistan is also facing fiscal deficit and trade deficit since its independence, so it relies on public debt to fill this fiscal gap. Objectives: The objective of this study is to estimate the optimal level of public debt for economic growth. Methods: This study explores the nonlinear relationships between public debt and economic growth of Pakistan by using time series data. The ARDL bound test technique is used to estimate the short-run and long-run impact of debt on economic growth. The growth maximizing level of debt is also estimated. Results: According to the estimated parameters, the optimal level of public debt is 60% of GDP. It also indicates that increase in government borrowings will raise economic growth in Pakistan in the long run. However, in the short run, if public debt increases it will boost economic growth after some levels of public debt and it will start declining. Conclusions: This study implies that public debt must be discouraged beyond optimal level of debt, as above optimal level it adversely affects the economic growth. Implications: The implication of the findings of the study is that higher interest rate curbs economic growth, therefore, present policy of keeping high interest rate by government should be revisited. Recommendations: Government of Pakistan should focus on fiscal and current account deficit, which are the main cause of increasing public debt, because higher public debt is not good for economic growth. Also, suitable fiscal policy is needed to control the debt burden and to get rid-off Ponzi game of debt from Pakistan by strictly enforcing the Fiscal Responsibility and Debt Limitation Act 2005.